(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
Educational and political theorists have argued that education for democratic citizenship, whether at the K-12 level or in adult or higher education, should focus on fostering communicative capacities. For example, Jack Mezirow has used the work of Jürgen Habermas to emphasize the importance of fostering communicative reason in democratic and emancipatory adult education. John Dryzek argues in general terms that “literacy and education facilitate deliberative capacity inasmuch as they influence the communicative competence of political actors and ordinary citizens.” Amy Gutmann argues that all levels and types of education—education within the family context, K-12 schooling, higher education, and adult and informal education—should “aim … to teach the skills and virtues of democratic deliberation.” And Tomas Englund draws on a neopragmatist interpretation of John Dewey’s work to argue for “the need to develop deliberative capabilities in schools."